2023
DOI: 10.1021/acs.biomac.2c01488
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(allyl glycidyl ether)-Derived Polyampholytes and Their Application to the Cryopreservation of Living Cells

Abstract: Through the postpolymerization modification of poly(allyl glycidyl ether) (PAGE), a functionalizable polyether with a poly(ethylene oxide) backbone, we engineered a new class of highly tunable polyampholyte materials. These polyampholytes can be synthesized to have several useful properties, including low cytotoxicity and pH-responsive coacervate formation. In this study, we used PAGE-based polyampholytes (PAGE-PAs) for the cryopreservation of mammalian cell suspensions. Typically, dimethyl sulfoxide (DMSO) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…PVA exhibited a very high IRI activity, and very small ice crystals were formed from the PVA solution (Figure a). The ice crystal size was semiquantitatively analyzed by MLGS (Figure b). Compared with that of PBS without polymers, PATs-1 and PATs-2 had approximately 49% of MLGS, whereas PATs-3 and PATs-4 had 31% of MLGS in 10.0 mg/mL solutions. IRI activities were similar for PATs-1 and PATs-2 group and PATs-3 and PATs-4 group, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…PVA exhibited a very high IRI activity, and very small ice crystals were formed from the PVA solution (Figure a). The ice crystal size was semiquantitatively analyzed by MLGS (Figure b). Compared with that of PBS without polymers, PATs-1 and PATs-2 had approximately 49% of MLGS, whereas PATs-3 and PATs-4 had 31% of MLGS in 10.0 mg/mL solutions. IRI activities were similar for PATs-1 and PATs-2 group and PATs-3 and PATs-4 group, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that a low-molecular ZI strongly interacts with cell membranes through an electrostatic interaction 16 . Since the polyZI does not interact strongly with water, the polyZI was expanded by the addition of NaCl and then strongly interacts with the cell membrane 29 , 30 and forms matrices.
Fig.
…”
Section: Resultsmentioning
confidence: 99%